A competitive dual recycling channel in a three-level closed loop supply chain under different power structures: Pricing and collecting decisions. (1st November 2020) - Ranjbar, Yahya; Sahebi, Hadi; Ashayeri, Jalal; Teymouri, Ashkan
Abstract: The past two decades witnessed the raise of closed-loop supply chain due to huge attention to the environment and business social responsibility. Both academia and industry have examined recycling and remanufacturing of the used products, due to these concerns complicated by resource scarcity, and government regulations. In this paper, a three-level closed-loop supply chain consisting of a manufacturer, retailer, and third-party collector are considered. The manufacturer builds simultaneously new products from raw materials and remanufactures the returning products. The main idea of the study is to evaluate optimal pricing and collection decisions under channel leadership with two competitive recycling channels including retailer collecting and third-party collector collecting. Based on game theory, four different scenarios are developed - a centralized model and three decentralized models based on the Stackelberg game including Manufacturer Stackelberg, Retailer Stackelberg, and third-party collector Stackelberg. To verify the model, the real case of a TV set producer is studied and then the optimal decisions compared and analyzed in different scenarios. The effect of competition between the retailer and the third-party collector recycling channel has been examined on decision variables, member profits and total profit. A comprehensive sensitivity analysis has been carried out considering the base market size parameter and the sensitivity of demand to retail prices. The examination of the results from the environmental and consumer welfare aspects shows that the retailer leadership decentralized model is often the most effective scenario in closed-loop supply chain, and considering the overall benefit of the supply chain between decentralized models, the retailer leadership model is the best and closest model to the centralized model. Highlights: Studying pricing and collecting decisions in this CLSC with competitive dual recycling channel. Formulating a three-echelon CLSC model with two reverse channels including retailer and TPC collecting. Comparing different channel leaderships to optimize the consumer value,  environmental effects and profit performance. Analyzing sensitivity of the competition intensity between retailer and TPC collecting channels. Validating the proposed model by solving a real case study of a TV set manufacturer under different conditions in a CLSC.